The LIFE-GARACHICO Project: A Holistic and Flexible Management of Coastal Flooding Risk in Praia da Vitória, Azores - Larize Lima; Conceição J. E. M. Fortes; Ana Catarina Zózimo; Liliana V. Pinheiro (GeoHazards, 2025)
This research addresses the increasing vulnerability of coastal urban areas to climate change, with a particular focus on the increased risk of overtopping and coastal flooding events in Praia da Vitória, Azores. This study, conducted within the LIFE-GARACHICO project, aims to develop a holistic and flexible management approach to coastal flood risk. The methodology included a comprehensive risk assessment that combined a vulnerability analysis (considering factors such as population, land use, and infrastructure) with the probability of coastal inundation events (using oceanographic data and models). Public risk perception was assessed through surveys to understand residents’ awareness and preferences. A response protocol for overtopping events was developed with civil protection officials, and the HIDRALERTA early warning system was implemented. The risk assessment showed a mostly acceptable risk with some undesirable areas, resulting from a mostly low probability and medium vulnerability. Public surveys indicated that residents had experienced flooding but felt unprepared and preferred softer management measures such as access restrictions and early warning systems. The response protocol developed and integrated into HIDRALERTA responds to these preferences. This study concludes that this integrated framework improves coastal risk management, increases public awareness and confidence, and provides a flexible and sustainable model for coastal risk management.